N-Butylpyridinium undecachlorocarbadodecaborate and comparison with similar compounds - Suarez, S.A. (2011)
The title compound, C 9H 14N +· CHB 11Cl 11 -, was obtained in the course of our continuing studies of the low-melting salts of closo- and nido-carborane cage anions with alkyl-pyridinium and dialkyl-imidazolium cations. The title compound is the first example of a pyridinium salt of a perchlorinated carborane anion. The structure consists of one N-butyl-pyridinium cation counterbalanced by one perchlorinated carborane cage anion per asymmetric unit. By changing the counter-ion, different packings are observed, and to try to understand this the new structure is compared with five similar compounds. © 2011 International Union of Crystallography.